Game theory and the law: rule interactive interpretation - Flores Borda, Guillermo (2014)
Until this point, most research works have focused on how bad design of legal rules ay lead to opportunistic strategic behavior. This paper intends to show that even well-designed rules may lead to opportunistic strategic behavior due to bad communication of the “reasonability” of the legal rule, as well as to provide a definition of “reasonability” (i.e., good design) of the legal rules.This paper also intends to show how the personal interpretation of each player with respect to the strategy set and payoff structure of a legal rule impacts social interac- tion producing suboptimal social outcomes.